Impactul inteligenței artificiale asupra procesului educațional [Articol] - Darii, Olga; Beldiga, Maria (CEP USM, 2024)
This study conducted a thorough content analysis of research investigating the integration of artifcial intelligence (aI) in education. Its aim was to uncover trends, challenges, and potential applications of aI in the educational context. The analysed methods encompassed teaching enhancements (concept visualization, digital lesson creation), adaptive learning (smart learning companions, personalized learning systems), and evaluation tools (plagiarism detection). additionally, a theoretical case study was introduced, proposed for empirical examination. The study also highlighted potential challenges posed by aI in education, including concerns over its inappropriate use, changing educator and student roles, technical barriers, and resistance to change. The fndings contribute to a comprehensive understanding of aI in education, bolstering its theoretical basis, fostering collaboration between educators and aI experts, and providing a solid groundwork for empirical case studies.
THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE EDUCATIONAL PROCESS
DARII, Olga, BELDIGA, Maria. Impactul inteligenței artificiale asupra procesului educațional. In: Integrare prin cercetare și inovare: conferința științifică națională cu participare internațională. Ştiinţe ale naturii și exacte, 9-10 noiembrie 2023. CEP USM, 2024, pp. 610-618. ISBN 978-9975-62-690-3.
Keywords: inteligența artifcială; învățare adaptivă; proces educational; vizualizarea conceptelor